Line loss analysis and calculation of electric power systems - Wu, Anguan; Ni, Baoshan (Singapore : Wiley, 2015)
Presents the fundamentals and calculation of transmission line losses, their reduction, and economic implications - Written by a very experienced expert in this field- Introduces various technical measures for loss reduction, and appended with a large number of examples- Offers a progressive and systematic approach to various aspects of the problems- A timely and original book to meet the challenges of power and grid industry development.
Calculation of Line Loss by Current Load Curve -- Probability Theory Analysis of Current Load Curve -- Calculation of Line Loss by Power Load Curve -- Line Loss Calculation after Reactive Compensation -- Change Law for the Electric Energy Losses of Power Grids -- Analysis and Control of Line Loss Rate Indicators of Power Grids -- Theoretical Calculation of Electric Energy Losses of Power Grid Units -- Calculation of Electric Energy Losses of Multi-branch Lines -- Calculation of High-voltage Power Grid Losses -- Analysis and Calculation of Loss Allocation -- Technical Measures for the Reduction of Line Losses -- Line Loss Prediction and Loss Reduction Plan for Power Grids -- Analysis of the Influence of Power Grid Line Losses on Power Grid Enterprises -- Management and Utilization of Line Loss Mass Information for an Electric Power System -- Appendix A Calculation Curve of Corona Loss Power [delta] -- Appendix B Calculation of Electrical Parameters of Power Grid Units -- Appendix C Derivation of Loss Factor Formula by Subsection Integration Method -- Appendix D Actual Measurement Analysis of No-load Power Losses and Relationship between No-load Current and Voltage of Distribution Transformers.
Includes bibliographical references and index.
Online resource; title from PDF title page (John Wiley, viewed November 24, 2015).
Keywords: Electric power systems -- Electric losses -- Mathematical models; Electric power systems -- Load dispatching -- Mathematics; Electric lines; Electric resistance; Electronic books